Ответы и объяснения

2014-03-09T20:53:55+00:00
Лучший Ответ!
  • Участник Знаний
2014-03-09T21:05:31+00:00
39.24.
1)lim√2x-6=√2*3,5-6=√7-6=√1=1
2)=(5+2)/(3+2+4)=7/9
39.27
1)=limx(x-3)/(x-3)=limx=3
2)=lim(x+5)/x(x+5)=lim1/5=1/5
39.28
1)=lim(x-5)(x+5)/(x-5)=lim(x+5)=(5+5)=10
2)=lim(3+x)/(x+3)(x-3)=lim1/(x-3)=1/(-3-3)=-1/6
39.29
1)lim(x+1)/(x-3)(x+1)=lim1/(x-3)=1/(-1-3)=-1/4
x²-2x-3=0
x1+x2=2 U x1*x2=-3⇒x1=3 U x2=-1⇒x²-2x-3=(x-3)(x+1)
2)x²-11x+18=0
x1+x2=11 U x1*x2=18⇒x1=9 U x2=2, x²-11x+18=(x-9)(x-2)
lim(x-9)(x-2)/(x-9)=lim(x-2)=9-2=7